Biblical ambiguities : metaphor, semantics, and divine imagery - Aaron, David H., 1956- (Brill reference library of ancient Judaism ;, 2001)
This volume poses as its central question: when we read a passage in the Hebrew Bible, how do we know whether the passage was meant literally or metaphorically? This study argues that our assumptions as to how language works influences the way we interpret biblical texts.